2012
DOI: 10.1016/j.molmed.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

CFTR: folding, misfolding and correcting the ΔF508 conformational defect

Abstract: Cystic fibrosis (CF), the most common lethal genetic disease in the Caucasian population, is caused by loss-of-function mutations of the CF transmembrane conductance regulator (CFTR), a cyclic AMP-regulated plasma membrane chloride channel. The most common mutation, deletion of phenylalanine 508 (ΔF508), impairs CFTR folding and, consequently, its biosynthetic and endocytic processing as well as chloride channel function. Pharmacological treatments may target the ΔF508 CFTR structural defect directly by bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
327
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(335 citation statements)
references
References 99 publications
(157 reference statements)
6
327
0
2
Order By: Relevance
“…However, in another study, overexpression of F508del‐CFTR was reported to increase XBP1 splicing, suggesting that the mutant protein can increase ER stress 7. In considering the influence of the mutated protein, it is important to take into account that a large proportion (~60–80%) of wild‐type CFTR misfolds during biosynthesis due to the protein's complex transmembrane and nucleotide‐binding domains48; consequently, there will be a background of compensatory UPR activation in all CFTR‐expressing cells. The key question is whether the increased misfolding in the case of mutant CFTR substantially disturbs the state of proteostasis normally achieved in these respiratory epithelial cells.…”
Section: Oxidative and Er Stress In Chronic Inflammatory And Mucopurumentioning
confidence: 99%
“…However, in another study, overexpression of F508del‐CFTR was reported to increase XBP1 splicing, suggesting that the mutant protein can increase ER stress 7. In considering the influence of the mutated protein, it is important to take into account that a large proportion (~60–80%) of wild‐type CFTR misfolds during biosynthesis due to the protein's complex transmembrane and nucleotide‐binding domains48; consequently, there will be a background of compensatory UPR activation in all CFTR‐expressing cells. The key question is whether the increased misfolding in the case of mutant CFTR substantially disturbs the state of proteostasis normally achieved in these respiratory epithelial cells.…”
Section: Oxidative and Er Stress In Chronic Inflammatory And Mucopurumentioning
confidence: 99%
“…This process, termed ER-associated protein degradation (ERAD) 1,2 , is pivotal for the maintenance of cellular homeostasis and its mechanistic exploration will contribute to the treatment of various neurodegenerative disorders [3][4][5] and folding diseases like cystic fibrosis 6,7 . Key components of ERAD are large multi-subunit ubiquitin ligases, which are embedded in the ER-membrane 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Distinct E3 ubiquitin ligases have been identified that are involved in ⌬F508-CFTR ubiquitination (34,35). DNAJB12, HSPA8 (Hsc70), and RNF5 (RMA1) are involved in co-translational ubiquitination of ⌬F508-CFTR (36, 37), whereas CHIP (STUB1) is involved with ubiquitination of full-length ⌬F508-CFTR (36,38).…”
Section: Rna Interference Screen Of 13 Candidates Reveals Role For Symentioning
confidence: 99%
“…DNAJB12, HSPA8 (Hsc70), and RNF5 (RMA1) are involved in co-translational ubiquitination of ⌬F508-CFTR (36, 37), whereas CHIP (STUB1) is involved with ubiquitination of full-length ⌬F508-CFTR (36,38). RNF5 (E3 ubiquitin-protein ligase) and AMFR (Gp78; E3 ubiquitin-protein ligase) are integral to the ⌬F508-CFTR ubiquitination machinery in the ER (34,37). AMFR complexes with RNF5 and specifically promotes polyubiquitination of ⌬F508-CFTR (35).…”
Section: Rna Interference Screen Of 13 Candidates Reveals Role For Symentioning
confidence: 99%